2016
DOI: 10.1038/ni.3421
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 1 is an innate lymphoid-cell-intrinsic metabolic checkpoint controlling type 2 inflammation

Abstract: Group 2 innate lymphoid cells (ILC2s) regulate tissue inflammation and repair following activation by cell-extrinsic factors including host-derived cytokines. However, the cell-intrinsic metabolic pathways that control ILC2 function are undefined. Here we demonstrate that expression of the enzyme Arginase 1 (Arg1) is a conserved trait of murine and human ILC2s during acute or chronic lung inflammation. Deletion of murine ILC-intrinsic Arg1 abrogated type 2 lung inflammation by restraining ILC2 proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
249
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(267 citation statements)
references
References 49 publications
17
249
0
1
Order By: Relevance
“…Studies of lung regeneration after partial pneumonectomy support the concept that interactions among activated macrophages and lung parenchymal cells create a proliferative microenvironment (22). In the present study, regeneration was associated with marked increase in inflammatory cell expression of ARG1 and other markers of atypical macrophage activation (M2-like), including RETNLA and CD206, proposed to contribute to repair processes (22,41,42). Alveolar macrophages expressing CD206 and ARG1 were identified by immunofluorescence confocal microscopy in both Abca3-cKO mouse lung during regeneration and in lung tissue from patients with severe lung disease caused by ABCA3 mutations.…”
Section: Discussionsupporting
confidence: 71%
“…Studies of lung regeneration after partial pneumonectomy support the concept that interactions among activated macrophages and lung parenchymal cells create a proliferative microenvironment (22). In the present study, regeneration was associated with marked increase in inflammatory cell expression of ARG1 and other markers of atypical macrophage activation (M2-like), including RETNLA and CD206, proposed to contribute to repair processes (22,41,42). Alveolar macrophages expressing CD206 and ARG1 were identified by immunofluorescence confocal microscopy in both Abca3-cKO mouse lung during regeneration and in lung tissue from patients with severe lung disease caused by ABCA3 mutations.…”
Section: Discussionsupporting
confidence: 71%
“…IL-25 and IL-33 both upregulated genes associated with ILC2 activation, including Il5 , Klrg1 , and Arg1 , while other genes, such as Areg , were preferentially induced by one alarmin but not the other (Extended Data Fig. 1i) 2,16 .…”
Section: Alarmins Induce Heterogeneity In Ilc2smentioning
confidence: 99%
“…Myeloid cell Arg1 has immunosuppressive capacities (Rodriguez et al 2004;Munder et al 2006), and, recently, Arg1 was shown to perform a cell-intrinsic role in the regulation of ILC2 metabolism and type 2 inflammation in the lung (Monticelli et al 2016).…”
Section: Metabolites As Regulators Of Symbiosismentioning
confidence: 99%